Al-Tabdīl wa al-Takhlīṭ al-Lugawī baina al-‘Arabiyyah wa al-Jāwiyyah fī al-Muhādaṡāt al-Yaumiyyah li Tullāb al-Ma’had - Hidayah, Fatma Nurul; Nasir, Amin (Study Program of Arabic Language Teaching, 2026)
The purpose of this study is to describe the characteristics of code-switching and code-mixing in everyday conversations at the Darussalam Al-Akhyar Islamic Boarding School in Kudus. The method used in this study is qualitative descriptive. The data collection techniques used were observation, documentation, audio recording, and field notes. The data source of this study was the daily conversations of female students at Darussalam Al-Akhyar Islamic Boarding School in Kudus. Data were collected through documentation using the listening recording, and note-taking techniques. The findings indicate that students frequently use code-switching and code-mixing in daily conversations. Code-switching consists of internal and external types, while code-mixing is also categorized into internal and external forms, with each occurring according to the conversational context. Internal code-switching occurs when shifting from Javanese to Arabic and from Arabic to Javanese in certain conversational situations. External code-switching, on the other hand, occurs through the use of foreign language elements other than Javanese and Arabic in interactions among santri. Internal code-mixing occurs through the insertion of Javanese elements into Arabic speech or of Arabic elements into Javanese speech. Meanwhile, external code-mixing occurs through the insertion of elements from other foreign languages into the daily conversations of santri.